TUTOR INTI SEBAGAI SOLUSI PERCEPATAN PENINGKATAN KOMPETENSI TENAGA PENDIDIK NONFORMAL - Chairuddin Samosir (JIV-Jurnal Ilmiah Visi, 2008)
There is still a bad need to improve the competence of a large number of non-formal educators but the Government has limited budget and trainers to do formal trainings all over the country. This article purposes a cell system through a master tutor as an alternative training model to solve the problem. This model can be successfully implemented under sufficient support and supervision of The Education Office in district level, PTK-PNF Forum, BPKB, SKB and the Directorate of PTKPNF.